PUBLIC POLICY CONFLICTS IN INVESTOR-STATE ENERGY ARBITRATIONS (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Changing energy policy and a growing demand for environmental protection create public policy conflicts for states. There is a fundamental tension between the host state's right to regulate and an investor's expectation of a stable regulatory environment. New domestic laws for environmental protection may conflict with treaty obligations to protect pre-existing investments of foreign investors. A host state's obligation to protect investments through existing international treaties may conflict with international obligations under new multilateral agreements. This article discusses the resulting constraints on the state's ability to manoeuvre in the realm of energy policy in light of states' international and domestic obligations.